Electrodeposited silica film interlayer for active corrosion protection. (15th May 2017) - Liu, Yan-Hua; Xu, Jun-Bo; Zhang, Jin-Tao; Hu, Ji-Ming
Graphical abstract: A novel protective painting system has been proposed, in which a 10 μm-level thick and highly porous electrodeposited silica (e-SiO2 ) film is used simultaneously as the interlayer and the nanocontainers of inhibitors. The model coatings constructed provide superior protectiveness, because inhibitors release "in time" from interlayer to the corroded substrate. Highlights: A new coating system was proposed using electrodeposited silica film interlayer as the nanocontainer of inhibitors. The thick, highly porous and well adherent electrodeposited sol-gel film benefits the encapsulation of desired amount of corrosion inhibitors within. The new coating system is shown to significantly improve the corrosion resistance of mild steel substrate. Abstract: In the present work, a pragmatic painting system with promising active protection property is proposed using electrodeposited silica (e-SiO2 ) interlayer as the nanocontainer of inhibitors. A 10 μm thick, highly porous and well adherent sol-gel silica film was prepared at mild steel substrate under the aid of electro-assist technique. Such film was capable of embedding desired amount of corrosion inhibitors (polyvinylpyrrolidone and zinc gluconate), upon which the epoxy coating was covered. Both the accelerated corrosion tests on the scratched coating and the in-situ electrochemical measurements of intact sample revealed the significantly improved corrosion resistance of the novel coating system.